Perfil e trajetória de educadores em instituição de acolhimento infantil - CAVALCANTE, Lília Iêda Chaves (2013)
This study identified aspects of personal professional and institutional background, of shelter educators, as well as their perception and satisfaction with the activities conducted in one institution of this kind. We interviewed 102 teachers working in a child under the Metropolitan Region of Belém, whose profiles show that all respondents were young female, at most with 35 years old having children, who had completed or were attending an undergraduate course. The overall results show that despite the high level of education, the educators felt unprepared to deal with shettered children, what lead to the exclusion of care from Education. We need new strategies for in-service training should be designed in order to meet the demands placed by the technical guidelines for services for handicapped children, adopted in 2009.